A Severe Necrotizing Inflammatory Reaction of Leg Wounds Following Autologous Peripheral Blood Total Nucleated Cells Treatment in an Old Patient With Rheumatoid Arthritis and No-Option Chronic Limb-Threatening Ischemia: Is Cell Therapy Suitable for All Patients?. (March 2023) - Vallini, Valerio; Venturini, Luigi; Carnesecchi, Paolo; Andreini, Roberto; Meini, Simone
Chronic limb-threatening ischemia (CLTI) represents an unfavorable evolution of peripheral artery disease, characterized by pain at rest, ulceration, and gangrene and also by an increased risk of cardiovascular events, amputations, and death. According to scientific literature, in almost one third of cases affected by CLTI, defined as no-option CLTI patients, revascularization strategies are not feasible. In the past decade, several studies investigated the role of therapeutic angiogenesis through cell autologous therapy, administered through intramuscular injections or multiple local intralesional and perilesional injections. In this article, we report the case of a necrotizing inflammatory reaction in a patient affected by CLTI and chronic leg wounds that occurred on the multiple injection sites after autologous peripheral blood-derived mononuclear cells (PB-TNCs) transplantation. Since the patient was affected by corticosteroid-induced skin atrophy and rheumatoid arthritis, we hypothesize that an increased skin fragility and a mechanism of immune-mediated pathergy could have been main factors leading to worsening of wounds. This case report strongly suggests the urgent need to better define the indications and contraindications of cell therapy, and further studies of adequate methodology are required to definitively assess the efficacy and safety of autologous cell therapy by local injections of PB-TNCs in patients with chronic inflammatory disorder, such as rheumatoid arthritis, especially in case of concomitant marked skin atrophy. Pending definitive evidence from literature, a strong caution is needed in patients affected by chronic systemic inflammatory diseases, since multiple injections, acting as mechanical stimulus and pathergy trigger, might exacerbate a severe and uncontrolled inflammatory response.